Resuming social contact after months of contact restrictions: social traits moderate associations between changes in social contact and well-being - Krämer, Michael; Roos, Yannick; Richter, David; Wrzus, Cornelia (Journal of research in personality, 2022)
Humans possess a need for social contact. Satisfaction of this need benefits well-being, whereas deprivation is detrimental. However, how much contact people desire is not universal, and evidence is mixed on individual differences in the association between contact and well-being. This preregistered longitudinal study (N = 190) examined changes in social contact and well-being (life satisfaction, depressivity/anxiety) in Germany during pervasive contact restrictions, which exceed lab-based social deprivation. We analyzed how changes in personal and indirect contact and well-being during the first COVID-19 lockdown varied with social traits (e.g., affiliation, extraversion). Results showed that affiliation motive, need to be alone, and social anxiety moderated the resumption of personal contact under loosened restrictions as well as associated changes in life satisfaction and depressivity/anxiety.